Women in pain : gender and morbidity in Mexico - Finkler, Kaja (University of Pennsylvania Press, 1994)
Why are Mexican women more likely to experience nonfatal diseases than their male counterparts? To unravel this mystery, Kaja Finkler explores the relationship between patterns of social interaction, cultural expectations, and gender ideologies. In Women in Pain, she examines the nature of sickness and its interaction with issues about gender and gender relations from both a historical and contemporary perspective. At the heart of Women in Pain are the life histories often women - most of them poor - who have suffered from chronic, nonfatal illnesses for extended periods. The women selected are very much individuals, but they are also representative of the larger sample from which they were chosen. Finkler shows how women's health issues are intertwined with social realities, cultural ideologies, and subjective evaluations. The women illuminate the subjective nature of sickness and how affliction is embedded in material and ideological webs. Finkler furnishes a fresh approach by weaving together the women's individual understandings about their lives, their distresses, their social circumstances, and their cultural beliefs. The resulting tapestry brings into bold relief aspects of their existence (including relationships with their mates) that pose dangers to their health. To give the reader a sense of how the women experience their pain, Finkler attends to the women's symptomatologies, to the bio-medical diagnoses they receive, to their health seeking trajectories, to the history of their symptoms, and to their biographies within the context of their anguish. She uses the concept of "life's lesions," defined roughly as the physical damage caused by cultural and social factors, to interpret the rich data gathered from her extensive fieldwork. While the focus is on the lives of Mexican women, the book speaks to women's existence in contemporary society in general, and to the theoretical concerns regarding gender and health. All those interested in gender issues, women's lives, and women's health issues in developing nations will find the book fascinating and rewarding reading.